Resveratrol impacts in oxidative stress in liver during Trypanosoma cruzi infection - Fracasso M. (2021)
© 2021 Elsevier LtdTrypanosoma cruzi is the causative agent of Chagas disease, infecting the heart, intestines and liver tissues. There is growing evidence that oxidative stress, defined as a persistent imbalance between highly oxidative compounds and antioxidant defenses, is a marker of tissue inflammation; it is related to immune responses such as damage, as well as to strand breaks in DNA contributing to disease progression. Antioxidant agents help mitigate the damage caused by inflammation, preventing or slowing damage to cells caused by free radicals. In this sense, resveratrol (RSV) is an important polyphenol that demonstrates antioxidant effects. It reverses damage caused by several infectious diseases. The aim of the present study was to determine whether treatment with RSV would prevent or minimize oxidative damage caused by T. cruzi. The animals were divided into four groups (n = 5): A) control; B) control + RSV; C) infected and D) infected + RSV. The infected groups received 1 x 104 Y strain trypomastigotes via intraperitoneal injection; after confirmation of infection, the mice received RSV 100 mg/kg for seven days orally. On the 8th day post-infection, we collected liver tissue for analysis of oxidant/antioxidant status: superoxide dismutase (SOD), catalase (CAT), and glutathione s-transferase (GST) activities, as well as reactive oxygen species (ROS), non-protein thiols (NPSH), thiols, carbonyl protein, thiobarbituric acid reactive substance (TBARS), and finally, the nitrite/nitrate ratio (NOx) levels were determined. The administration of RSV did not exert direct effect on parasitemia. The infection produced high levels of TBARS, NOx, and ROS levels in liver tissue, suggesting cellular injury with production of free radicals in animals infected by T. cruzi. RSV positively modulated SOD and aumenting GST activities enzymes in infected animals. Protein thiols levels in infected animals were lower than those of control. Taken together, the data suggest T. cruzi causes hepatic oxidative stress, and RSV 100 mg/kg for seven days it's dosen't seem minimized these negative effects in the acute phase of disease.